Light chain mutations contribute to defining the fibril morphology in systemic AL amyloidosis - Karimi-Farsijani, Sara; Pfeiffer, Peter Benedikt; Banerjee, Sambhasan; Baur, Julian; Kuhn, Lukas; Kupfer, Niklas; Hegenbart, Ute; Schönland, Stefan; Wiese, Sebastian Edgar; Haupt, Christian; Schmidt, Matthias; Fändrich, Marcus (Nature Communications, 2024)
Systemic AL amyloidosis is one of the most frequently diagnosed forms of systemic amyloidosis. It arises from mutational changes in immunoglobulin light chains. To explore whether these mutations may affect the structure of the formed fibrils, we determine and compare the fibril structures from several patients with cardiac AL amyloidosis. All patients are affected by light chains that contain an IGLV3-19 gene segment, and the deposited fibrils differ by the mutations within this common germ line background. Using cryo-electron microscopy, we here find different fibril structures in each patient. These data establish that the mutations of amyloidogenic light chains contribute to defining the fibril architecture and hence the structure of the pathogenic agent.
Gesehen am 29.11.2024